The role of Nef protein in the pathogenesis of HIV infection - Rajapaksa, U (2013)
Human Immunodeficiency virus (HIV-1) uses various mechanisms to evade immune recognition by cytotoxic T cells. Down-regulation of Human Leucocyte Antigen class I (HLA-I) by the viral protein Nef is one such important mechanism. HLA-A and B are believed to be down-regulated by Nef while HLA-C and E are not. The differences in down-regulation were due to sequence differences between alleles. I evaluated the functional significance of polymorphisms in the cytoplasmic domains of HLA-A and B in Nef mediated HIV-1 pathogenesis. HLA-B cytoplasmic alleles resisted down-regulation mediated by nef compared to HLA-A cytoplasmic alleles and these differences were seen to play a crucial role in maintaining CTL response as shown by live virus ELISPOT assays, viral suppression assays and CD107a secretion. Therefore, we propose that this relative resistance to Nef mediated down-regulation by HLA-B cytoplasmic allele contributes to the high efficacy and better control of HIV infection by HLA-B restricted CTLs. The partial resistance of HLA-B cytoplasmic domain was maintained in HIV-2 Nef alleles and sub group O HIV-1 viruses. The variability of the HLA-A and B susceptibility appeared to depend on the Nef allele while resistance of HLA-C was global. Substitution of 315DR316 to GG and truncation of C terminal amino acids play a role in mediating resistance to Nef. Possibly these amino acid changes lead to different molecular trafficking profiles as observed in wet lab methods, and changes to secondary protein structures as predicted by in silico methods resulting in partial resistance. In addition, the functional significance of CD4 down-regulation by Nef, another important effect was also explored in this thesis. Nef was found to be ineffective in down-regulating CD4 molecules truncated at cytoplasmic domain and the viruses which were produced in cell lines expressing truncated CD4, were found to be defective in terms of replication and infection. Evaluating the potential of these CD4 molecules in gene therapy is highlighted in my in vitro studies. In summary this thesis provides insight into important but unexplored areas of Nef mediated pathogenesis of HIV infection.